MEREKATKAN IMAJINASI BERSAMA: INISIATIF MEDIA CERITA RAKYAT BAHASA MARORI MEN GEY DI KAMPUNG WASUR KABUPATEN MERAUKE PROVINSI PAPUA - Ngurah Suryawan (Journal Social and Humaniora, 2017)
This article describes an initiative raised by young people from ethnic communities Marori Gey Men in Kampung Wasur Merauke to collect folklore as educational media and cultural customs. Language Marori Men practical Gey has lost an active speaker among young children. Folk stories told by elders to contain relations historically complex between the Marori Men Gey with Dema, their ancestors and with Mbur, old hamlet and the natural environment such as the hamlet of sago and wood believed to be the place of residence of the ancestors to protect their o?spring in the village , The values reflect the cultural knowledge of human relationships with the natural environment and ancestral started excluded in conjunction with the inability of young children to imbibe values in the language of folklore Marori Men Gey. Insistence socio-cultural changes brought by the timber loggers who exploit timber hamlets with the seduction of money makes people Marori Men Gey to think pragmatically who sacrificed their timber village. In this situation the Marori Men Gey lost his imagination to move ahead. This article studied education movement of young people to glue their imagination about the history and the world of the Marori Men Gey to respond to the insistence of social change inevitable. Keywords: initiatives, media education, knowledge of cultural, socio-cultural changes, imagination